Long-Term Outcomes of Genetic Parkinson’s Disease - Aasly, Jan O. (Journal of movement disorders, 2020)
Parkinson's disease (PD) is a progressive neurodegenerative disorder that affects 1-2% of people by the age of 70 years. Age is the most important risk factor, and most cases are sporadic without any known environmental or genetic causes. Since the late 1990s, mutations in the genes SNCA, PRKN, LRRK2, PINK1, DJ-1, VPS35, and GBA have been shown to be important risk factors for PD. In addition, common variants with small effect sizes are now recognized to modulate the risk for PD. Most studies in genetic PD have focused on finding new genes, but few have studied the long-term outcome of patients with the specific genetic PD forms. Patients with known genetic PD have now been followed for more than 20 years, and we see that they may have distinct and different prognoses. New therapeutic possibilities are emerging based on the genetic cause underlying the disease. Future medication may be based on the pathophysiology individualized to the patient's genetic background. The challenge is to find the biological consequences of different genetic variants. In this review, the clinical patterns and long-term prognoses of the most common genetic PD variants are presented.Parkinson's disease (PD) is a progressive neurodegenerative disorder that affects 1-2% of people by the age of 70 years. Age is the most important risk factor, and most cases are sporadic without any known environmental or genetic causes. Since the late 1990s, mutations in the genes SNCA, PRKN, LRRK2, PINK1, DJ-1, VPS35, and GBA have been shown to be important risk factors for PD. In addition, common variants with small effect sizes are now recognized to modulate the risk for PD. Most studies in genetic PD have focused on finding new genes, but few have studied the long-term outcome of patients with the specific genetic PD forms. Patients with known genetic PD have now been followed for more than 20 years, and we see that they may have distinct and different prognoses. New therapeutic possibilities are emerging based on the genetic cause underlying the disease. Future medication may be based on the pathophysiology individualized to the patient's genetic background. The challenge is to find the biological consequences of different genetic variants. In this review, the clinical patterns and long-term prognoses of the most common genetic PD variants are presented.